Escape routes from sovereign default risk in the euro area - Willi Semmler; Christian R. Proa\~no (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2015)
The recent financial and sovereign debt crises around the world have sparked a growing literature on models and empirical estimates of defaultable debt. Frequently households and firms come under default threat, local governments can default, and recently sovereign default threats were eminent for Greece and Spain 2012-13. Moreover, Argentina experienced an actual default in 2001. What causes sovereign default risk, and what are the escape routes from default risk? Previous studies such as Arellano (2008), Roch and Uhlig (2013) and Arellano et al. (2014) have provided theoretical models to explore the main dynamics of sovereign defaults. These models can be characterized as threshold models in which there is a convergence toward a good no-default equilibrium below the threshold and a default equilibrium above the threshold. However, in these models aggregate output is exogenous, so that important macroeconomic feedback effects are not taken into account. In this paper, we 1) propose alternative model variants suitable for certain types of countries in the EU where aggregate output is endogenously determined and where financial stress plays a key role, 2) show how these model variants can be solved through the Nonlinear Model Predictive Control numerical technique, and 3) present some empirical evidence on the nonlinear dynamics of output, sovereign debt and financial stress in some euro area and other industrialized countries.
urn:nbn:de:bsz:180-madoc-388654
Keywords: E44; E62; H63; 330; sovereign default risk; financial stress; macroeconomic dynamics; euro crisis